Economic gains and health benefits from a new cigarette tax scheme in Taiwan: a simulation using the CGE model - Lee Jie-Min; Ye Chun-Yuan; Chen Sheng-Hong (BMC, 2006)
Abstract Background This study evaluates the impact of an increase in cigarette tax in Taiwan in terms of the effects it has on the overall economy and the health benefits that it brings. Methods The multisector computable general equilibrium (CGE) model was used to simulate the impact of reduced cigarette consumption resulting from a new tax scheme on the entire economy gains and on health benefits. Results The results predict that because of the new tax scheme, there should be a marked reduction in cigarette consumption but a notable increase in health benefits that include saving between 28,125 and 56,250 lives. This could save NT$1.222~2.445 billion (where US$1 = NT$34.6) annually in life-threatening, cigarette-related health insurance expenses which exceeds the projected decrease of NT$1.275 billion in Gross Domestic Product (GDP) because of reduced consumption and therefore tax revenue. Conclusion Overall, the increased cigarette excise tax will be beneficial in terms of both the health of the general public and the economy as a whole.